Pathogen frequency and resistance patterns in Brazilian hospitals: summary of results from three years of the SENTRY antimicrobial surveillance program - Helio S. Sader; Ana C. Gales; Michael A. Pfaller; Rodrigo E. Mendes; Cássia Zoccoli; Afonso Barth; Ronald N. Jones (Brazilian Journal of Infectious Diseases)
BACKGROUND: Pathogen frequency and resistance patterns may vary significantly from country to country and also in different hospitals within a country. Thus, regional surveillance programs are essential to guide empirical therapy and infection control measures. METHODS: Rank order of occurrence and antimicrobial susceptibility of pathogenic species causing bloodstream infections (BSI), lower respiratory tract infections (LRTI), wound or skin and soft tissue infections (WSSTI), and urinary tract infections (UTI) in hospitalized patients were determined by collecting consecutive isolates over a specified period of time, as part of the SENTRY Antimicrobial Resistance Surveillance Program (SENTRY). All isolates were tested by reference broth microdilution. RESULTS AND CONCLUSIONS: A total of 3,728 bacterial strains were obtained from January, 1997, to December, 1999, from 12 Brazilian hospitals located in 4 states. The largest number of isolates were obtained from patients with BSI (2,008), followed by LRTI (822 cases), UTI (468 cases), and WSSTI (430 cases). Staphylococcus aureus was the most frequently isolated pathogen in general (22.8% - 852 isolates), followed by E. coli (13.8% - 516 cases) and Pseudomonas aeruginosa (13.3% - 496 cases). Staphylococcus aureus was also the most common species isolated from BSI (23.6%) and WSSTI (45.8%), and P. aeruginosa was the most frequent species isolated from patients with LRTI (29.4%). The main bacterial resistance problems found in this study were: imipenem resistance among P. aeruginosa (69.8% susceptibility) and Acinetobacter spp. (88.1% susceptibility); ESBL production among K. pneumoniae (48.4%) and E. coli (8.9%); resistance to third generation cephalosporins among Enterobacter spp. (68.1% susceptible to ceftazidime) and oxacillin resistance among S. aureus (34.0%) and coagulase negative staphylococci (80.1%). Only the carbapenems (88.1% to 89.3% susceptibility) showed reasonable activity against the Acinetobacter spp. isolates evaluated.